Coregulatory mechanism and interactome network of miRNA, lncRNA, and mRNA involved in Human Diseases - Archit Gupta, Habeeb Shaik Mohideen, Raman Chandrasekar (Journal of Applied Pharmaceutical Science, 2024)
The enigmatic nature of non-coding RNA (ncRNA) continues to be a subject of profound intrigue in the field of biological systems. Among the diverse classes of ncRNAs, micro-RNAs (miRNAs) and long non-coding RNAs (lncRNAs) stand out as ubiquitous and integral components of cellular machinery. These RNA molecules orchestrate critical roles in a wide array of cellular processes. At the heart of their significance lies the intricate interplay between messenger RNAs (mRNAs), lncRNAs, and miRNAs, forming a highly sophisticated regulatory network that underpins gene expression. It is imperative to unravel these intricate interactions to grasp the multifaceted mechanisms governing gene expression regulation. This study is squarely focused on shedding light on the convoluted web of relationships involving microRNAs, long non-coding RNAs, and messenger RNA molecules. This multifaceted network of interactions plays a pivotal role in the regulation of the proteome, ultimately shaping the cellular phenotype. Understanding this complex regulatory system is not just an academic pursuit; it is crucial for comprehending the underlying mechanisms that drive cellular behavior. Beyond the fundamental aspects of cellular biology, this study ventures into the realms of human health and disease. It delves into the associations between these molecular interactions and the development of malignancies, cardiovascular disorders, and neurological conditions. By doing so, it provides valuable insights into potential therapeutic targets and intervention strategies. Additionally, this paper introduces an in-depth analysis of competitive endogenous RNA (ceRNA) networks, emphasizing their significant roles in the etiology of various human diseases. These networks are potential targets for pharmacological interventions to enhance human lifespan, promote health, and improve overall well-being. The intricate world of RNA is a frontier where science and health intersect, offering exciting possibilities for future research and therapeutic development.
Keywords: miRNA, lncRNA, mRNA interactions, ncRNA in human diseases